Boshnjaks. In other words: Jihad vs. McWorld and other theories... - Pilarska, Justyna (Journal of Education Culture and Society, 2020)
The Ottoman invasion of the Balkans that began in the 14th century led to an imbalance in the process of self-identification among the Bosnian people, having crucial influence on the process of establishing their sense of belonging, identification and national awareness. It particularly influenced the process of conceptualizing the cultural identity of Boshnjaks, whose ancestors converted to Islam and changed the ethnic and religious landscape of Balkans to a large extent. The author focuses on the political and social factors determining the shape of Bosnian identity, its origin and historical circumstances which influenced not only identification processes but also the course of the conflict in the Balkans between 1992 and 1995. This paper also provides data on many controversial facts regarding influences of Islamic radicals on Bosnian society before and after the fall of Yugoslavia. On the basis of social and historical analysis the author indicates that contemporary theories on cultural origin of conflicts, reduced to the dichotomy Jihad vs. McWorld are not applicable in the case of the unique, multicultural identity of Bosnian Muslims.